Disentangling plasma interaction and induction signatures at Callisto: The Galileo C10 flyby. Issue 9 (23rd September 2016) - Liuzzo, Lucas; Simon, Sven; Feyerabend, Moritz; Motschmann, Uwe
Abstract: We apply a combination of data analysis and hybrid modeling to study Callisto's interaction with Jupiter's magnetosphere during the Galileo C10 flyby on 17 September 1997. This encounter took place while Callisto was located near the center of Jupiter's current sheet. Therefore, induction in Callisto's subsurface ocean and magnetospheric field line draping around the moon's ionosphere both made nonnegligible contributions to the observed magnetic perturbations. The induction signal during C10 was obscured by plasma currents to a significant degree, in contrast to previously studied Callisto flybys. Our analysis reveals that at large distances to Callisto, its magnetic environment was dominated by field line draping, leading to the formation of Alfvén wings. Closer to the surface and in Callisto's wake, Galileo encountered a quasi‐dipolar "core region" that was partially shielded from the plasma interaction and was dominated by the induced field. When exiting this core region, the spacecraft crossed a rotational discontinuity where the magnetic field vector rotated by approximately 50°. The hybrid model is able to quantitatively explain numerous key features of the observed magnetic signatures, especially the transitions between draping‐ and dipole‐dominated regimes along the C10 trajectory. The model also reproduces the electron number density enhancement by 3–4 orders of magnitude detected in Callisto's wake, requiring a substantial ionosphere to surround the moon during C10. For flybys with nonnegligible plasma currents, comprehensive knowledge of the incident flow conditions and properties of Callisto's atmosphere is required to refine existing constraints on the subsurface ocean (conductivity, thickness, and depth) based on magnetic field data. These findings are highly relevant for the upcoming JUpiter ICy moon Explorer (JUICE) mission, which will include multiple Callisto flybys. Key Points: First study of Callisto's magnetic environment including contributions from its plasma interaction and induction within its subsurface ocean Induction dominates the magnetic environment in a "core region" of Callisto's wake; plasma interaction dominates farther from the moon Comprehensive knowledge of ambient plasma conditions is required to adequately refine existing constraints on Callisto's subsurface ocean